THE POTENTIAL OF STRATEGIC COALITIONS OF ALL-EMERGING COUNTRIES IN THE NEW GEOPOLITICAL ORDER - Iskandarsyah Siregar; Awang Azman bin Awang Pawi (Journal of Social Political Sciences, 2026)
This study, affiliated with emerging countries, explores strategic partnerships among Indonesia, Malaysia, and Brunei in today’s global multipolar politics. It uses a linguistic approach, based on Critical Discourse Analysis and Corpus-Based Semantic Mapping. The research reviews 312 state-owned publications from 2024 to 2026 to analyse how language shapes geopolitical cooperation. The findings show significant semantic merging, with Indonesia and Malaysia converging the most. This indicates a shared, albeit asymmetric, discursive framework. Quantitative data reveal that framing and conceptual metaphor (38.2% and 29.5%, respectively) dominate rhetorical strategies. Qualitative analysis shows Indonesia as the main force, Malaysia as a mediator, and Brunei as maintaining order in its territory and nearby areas if needed. Triangulating the conclusions shows that higher semantic matching drives more regional mutual aid, especially in ASEAN terms post-2011. The corpus also contains 29 documents; discursive fragmentation weakens coalition cohesion by adding vagueness. The study introduces 'semantic matching' as a new way to measure and assess national behaviour in international politics. These findings highlight how emerging-country groups can build shared narratives that align with the global landscape